2016
DOI: 10.1097/dbp.0000000000000281
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Self-Regulation from Birth to 7 Years

Abstract: Sleep problems in children with and without ADHD are associated with emotional dysregulation, which in turn contributes to poorer attentional functioning. This study highlights the importance of assessing and managing sleep problems in young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 54 publications
2
18
0
Order By: Relevance
“…It is important to intervene early with children who demonstrate early behavior risk at 4 years, including sleep problems, emotional dysregulation (high reactivity) and hyperactive-impulsive behaviors as measured in the current study as part of child behavioral risk. Other research (Williams and Sciberras, 2016; Williams et al, 2017) indicates the reciprocal relations among these behaviors from an early age. Sleep problems across the early childhood period, in particular, may drive and exacerbate emotional and attentional dysregulation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is important to intervene early with children who demonstrate early behavior risk at 4 years, including sleep problems, emotional dysregulation (high reactivity) and hyperactive-impulsive behaviors as measured in the current study as part of child behavioral risk. Other research (Williams and Sciberras, 2016; Williams et al, 2017) indicates the reciprocal relations among these behaviors from an early age. Sleep problems across the early childhood period, in particular, may drive and exacerbate emotional and attentional dysregulation.…”
Section: Discussionmentioning
confidence: 95%
“…Early childhood behavioral sleep problems have been linked with poorer attentional regulation (Williams and Sciberras, 2016; Williams et al, 2017) and executive function development over time (Bernier et al, 2013); and also poorer academic functioning (Quach et al, 2009). A recent analysis found that at 4–5 years, children with unresolved behavioral sleep problems, combined with above average levels of emotional dysregulation and poor attention were at higher risk for poor school adjustment (Williams et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that some children are sleeping less than the 10–13 h recommended by the American Academy of Sleep Medicine (4). Young children who sleep an insufficient number of hours are at risk for having adverse health problems (5), self-regulation problems (6), and learning difficulties (7). Preschool-age children who had sleep routines had a lower prevalence of obesity (8) and high social–emotional health (9).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is evidence that sleeping problems in infancy and toddlerhood are associated with self-regulation difficulties such as attention regulation and executive functioning (Bernier, Carlson, Bordeleau, & Carrier, 2010;Sadeh et al, 2015). Further, excessive crying persisting beyond 3 months of age and problems with feeding and sleeping in infancy have been associated with the development of behavior problems in childhood (Gurevitz et al, 2014;Hemmi et al, 2011;Hyde, O'Callaghan, Bor, Williams, & Najman, 2012;Korja et al, 2014;Sadeh et al, 2015;Santos et al, 2015;Schmid et al, 2010;Sivertsen et al, 2015;Williams & Sciberras, 2016), adolescence, and into adulthood (Sadeh, Tikotzky, & Kahn, 2014). This relationship may be strongest in those children who have multiple crying, feeding, and sleeping problems (Hemmi et al, 2011;Schmid et al, 2010;Wake et al, 2006;Winsper & Wolke, 2014).…”
mentioning
confidence: 99%